2021
DOI: 10.3390/ph14111144
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Anticancer Activity of Xanthone Derivatives: A Review

Abstract: The annual number of cancer deaths continues increasing every day; thus, it is urgent to search for and find active, selective, and efficient anticancer drugs as soon as possible. Among the available anticancer drugs, almost all of them contain heterocyclic moiety in their chemical structure. Xanthone is a heterocyclic compound with a dibenzo-γ-pyrone framework and well-known to have “privileged structures” for anticancer activities against several cancer cell lines. The wide anticancer activity of xanthones i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 208 publications
(263 reference statements)
1
43
0
Order By: Relevance
“…Cytotoxic phytocompounds present in different species of the genera Rollinia (Araujo et al, 2021;Cunha et al, 2009) and other annonaceous (George et al, 2021;Handayani & Yuzammi, 2021;Khan et al, 2020;Perrone et al, 2022;Rocha et al, 2021;Shehata et al, 2021) support the experimental results obtained here, with selective cytotoxic effect on normal cells (Ribeiro et al, 2018;Shehata et al, 2021). The antitumor action of xanthones and derivatives (Huang et al, 2021;Kurniawan et al, 2021;Nguyen et al, 2022;Pinto et al, 2021;Song et al, 2021Song et al, , 2022Zhao et al, 2022), and tannins (Musial et al, 2021;Shehata et al, 2021;Zeng et al, 2022;Zhang et al, 2021) also reinforces the data. Regarding the results exhibited by the phytochemical xanthone, new experimental tests need to be conducted to understand its cytotoxic action on cellular pathways as a function of the chemical groups (such as 1.7dihydroxy-xanthone) present in this polyphenol.…”
Section: Tablesupporting
confidence: 80%
See 1 more Smart Citation
“…Cytotoxic phytocompounds present in different species of the genera Rollinia (Araujo et al, 2021;Cunha et al, 2009) and other annonaceous (George et al, 2021;Handayani & Yuzammi, 2021;Khan et al, 2020;Perrone et al, 2022;Rocha et al, 2021;Shehata et al, 2021) support the experimental results obtained here, with selective cytotoxic effect on normal cells (Ribeiro et al, 2018;Shehata et al, 2021). The antitumor action of xanthones and derivatives (Huang et al, 2021;Kurniawan et al, 2021;Nguyen et al, 2022;Pinto et al, 2021;Song et al, 2021Song et al, , 2022Zhao et al, 2022), and tannins (Musial et al, 2021;Shehata et al, 2021;Zeng et al, 2022;Zhang et al, 2021) also reinforces the data. Regarding the results exhibited by the phytochemical xanthone, new experimental tests need to be conducted to understand its cytotoxic action on cellular pathways as a function of the chemical groups (such as 1.7dihydroxy-xanthone) present in this polyphenol.…”
Section: Tablesupporting
confidence: 80%
“…Xanthones polyphenols and their synthetic derivatives exhibit antitumor potential (Huang et al, 2021;Kurniawan et al, 2021;Pinto et al, 2021;Song et al, 2021Song et al, , 2022 and, interestingly, the treatment with RDLE that exhibits this phytochemical in its leaves, showed a very discrepant GI 50 . An investigation into a possible antagonistic effect among the extract's phytochemicals may clarify this result.…”
Section: Cytotoxicity Testmentioning
confidence: 99%
“…The anticancer activity of xanthones depends on the type, number, and position of the attached functional groups in their skeleton [ 47 ]. Anticancer activity of αM seems to depend on the presence of two isoprenyl groups localized on 2-nd and 8-th carbon in xanthenone ring [ 29 ], not present in vadimezan.…”
Section: Resultsmentioning
confidence: 99%
“…Castanheiro et al [ 48 ] showed that the introduction of the prenyl group to the 1-hydroxyxanthone markedly increased its anticancer activity against the MCF-7 cell line, in accordance with the presence of prenyl groups being associated with an improvement of potency and selectivity of xanthones [ 49 ]. At present, prenylated xanthones are the most valued xanthones, in view of their promising properties as active and selective anticancer agents [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to different substituents, xanthone derivatives can be divided into six categories, simple oxygenated xanthones, glycosylated xanthones, prenylated xanthones, xanthone dimers, xanthonolignoids, and miscellaneous xanthones. Prenylated xanthones are the most studied and widely concerned natural molecules, which exhibit more significant anticancer activity than other xanthones and have broad application prospects as possible and potential anticancer agents ( Kurniawan et al, 2021 ). With the interest in this class of compounds, cratoxylumxanthone C, a prenylated xanthone, was isolated from the plant C. cochinchinense , which had the prenyl substituent group, a key functional group for the anticancer activity of xanthone.…”
Section: Discussionmentioning
confidence: 99%